Designing and Modeling a Wireless Power Transfer System - Seyed Sajjad Mirakbari Jangali (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: Wireless power transfer systems have been rapidly increasing along with electronic devices while at the same time causing problems related to their power supplies. Using magnetic resonance coupling in wireless power transfer systems has been recognized as an appropriate technique for power supply of such devices. In this research, using this technique and applying the simulation results, attempts were made to meet a suitable balance between system efficiency and transfer distance through making a laboratory sample. Various factors can affect the efficiency of a wireless power transfer system, such as the changing of the output load, the shape of the transmitter and receiver coil, the wireless transfer distance, and changing of operating frequency. The results indicated that a relatively good efficiency can be achieved at a frequency close to the resonance system frequency and by matching the load impedance on the receiver side, while increasing the distance. Moreover, several samples of different types of transmitter and receiver coils were tested and the findings suggested that the shape of the coil was somewhat effective on the transfer distance.